Archetype and Hero’s Journey in Herman Hesse’s Demian - Ellsa Aringga Bahari (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2020)
Abstract This study aims to reveal the contribution of archetypes to Emil Sinclair's journey and illustrate the stages he has gone through during his journey from childhood to adulthood in this novel. Therefore, this study uses the structure of the Archetypal and Hero's Journey theory introduced by Joseph Campbell, with the concept of the Bildungsroman stage that has been elaborated by Kristy Littlehale. This research showed that five archetypes contributed to Sinclair's journey. Sinclair is a representation of the hero archetype. In contrast, the other two archetypes (Mentor and Herald) provide support and strength to Sinclair to start his adventure till adventure ends. The rest (Shapeshifter and Shadow) provide challenges and tests for Sinclair to make Sinclair learn more deeply about his life and be confident in his abilities. This study also found that in Demian, Sinclair experienced three stages consisting of twelve phases based on the hero's journey understanding. Sinclair's journey is also very much suitable for the four stages and characteristics of bildungsroman. Through the contribution of the archetypes and the stages that Sinclair had in advance, it can be concluded that each archetype has a significant role in the stages of Sinclair's journey to help him reach the end of the story and find his true identity. Keywords: Hero’s Journey, Archetypes, Bildungsroman, Self-identity, Journey Stages. Abstrak Studi ini bertujuan untuk mengungkap kontribusi dari arketipe-arketipe pada perjalanan Emil Sinclair serta mengilustrasikan tahapan yang telah ia lalui selama perjalanannya dari masa kecil hingga dewasa yang ada di dalam novel ini. Oleh karena itu, studi ini menggunakan struktur teori Archetypal dan Perjalanan pahlawan yang di kenalkan oleh Joseph Campbell, dengan konsep tahapan Bildungsroman yang telah di uraikan oleh Kristy Littlehale. Penelitian ini menunjukan bahwa ada lima arketipe yang berkontribusi pada perjalanan Sinclair. Sinclair menjadi representasi dari pahlawan. Sementara, dua arketipe lainnya (Mentor dan Herald) memberikan dukungan dan kekuatan untuk Sinclair sebagai seorang pahlawan untuk memulai petualangan hingga petualangannya berakhir. Sisanya (Shapeshifter dan Shadow) memberikan tantangan dan cobaan untuk Sinclair agar dia belajar lebih dalam tentang kehidupannya dan menjadi yakin dengan kemampuannya sendiri. Penelitian ini juga menemukan bahwa dalam Demian, Sinclair mengalami tiga tahapan yang terdiri dari dua belas fase berdasarkan pemahaman perjalanan pahlawan. Perjalanan Sinclair juga sangat sesuai dengan empat tahapan dan karakteristik dari bildungsroman. Melalui kontribusi arketipe dan tahapan yang telah di lalu Sinclair, dapat disimpulkan bahwa setiap arketipe memiliki peran yang signifikan terhadap tahapan-tahapan perjalanan Sinclair untuk membantunya mencapai akhir cerita dan menemukan jati dirinya. Keywords: Perjalanan Pahlawan, Arketipe, Bildungsroman, Jati diri, Tahapan perjalanan.